The Unique Properties of Placental Mesenchymal Stromal Cells: A Novel Source of Therapy for Congenital and Acquired Spinal Cord Injury - Edwin S Kulubya (MDPI AG, 2021)
Spinal cord injury (SCI) is a devasting condition with no reliable treatment. Spina bifida is the most common cause of congenital SCI. Cell-based therapies using mesenchymal stem/stromal cells (MSCS) have been largely utilized in SCI. Several clinical trials for acquired SCI use adult tissue-derived MSC sources, including bone-marrow, adipose, and umbilical cord tissues. The first stem/stromal cell clinical trial for spina bifida is currently underway (NCT04652908). The trial uses early gestational placental-derived mesenchymal stem/stromal cells (PMSCs) during the fetal repair of myelomeningocele. PMSCs have been shown to exhibit unique neuroprotective, angiogenic, and antioxidant properties, all which are promising applications for SCI. This review will summarize the unique properties and current applications of PMSCs and discuss their therapeutic role for acquired SCI.